2018 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2018
DOI: 10.1109/vr.2018.8446250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Representations for Typing in Virtual Reality

Abstract: Figure 1: Views on the conditions studied in the experiment on effects of hand representations for typing in VR. From left to right: NoHand, IKHand, Fingertip and VideoHand. AbstractAlphanumeric text entry is a challenge for Virtual Reality (VR) applications. VR enables new capabilities, impossible in the real world, such as an unobstructed view of the keyboard, without occlusion by the user's physical hands. Several hand representations have been proposed for typing in VR on standard physical keyboards. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 41 publications
0
57
0
Order By: Relevance
“…The virtual environment was showing the virtual keyboard and a monitor resting on a desk. In line with previous work [30,31] the passwords and the entered text were visualized both on the monitor and directly above the keyboard. The system was implemented in Unity 2018.2 and deployed on a PC (Intel Xeon E5-1650 processor, 64 GB RAM, Nvidia GTX 1070 graphics card) running Windows 10.…”
Section: Apparatus and Materialsmentioning
confidence: 85%
See 2 more Smart Citations
“…The virtual environment was showing the virtual keyboard and a monitor resting on a desk. In line with previous work [30,31] the passwords and the entered text were visualized both on the monitor and directly above the keyboard. The system was implemented in Unity 2018.2 and deployed on a PC (Intel Xeon E5-1650 processor, 64 GB RAM, Nvidia GTX 1070 graphics card) running Windows 10.…”
Section: Apparatus and Materialsmentioning
confidence: 85%
“…Grubert et al [30,31] investigated the performance of physical and touch keyboards and physical/virtual co-location for VR text entry. They proposed to use minimalistic fingertip rendering as hand representation and indicated that this representation is as efficient as a video-see through of the user's physical hands [30]. Subsequently, similar studies have investigated further hand representations, such as semi-transparent hand models [40].…”
Section: Physical Keyboards For Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…Another freedom VR provides is changing the representation and display of the user's hands in the virtual environment 10 . For example, the user's hands can become translucent in the virtual environment, which might provide an unobstructed view of the keyboard.…”
Section: Figurementioning
confidence: 99%
“…People are quite skilled at using keyboards in traditional desktop computing, but when wearing a head-mounted display (HMD) the lack of visual feedback makes typing more difficult [41,56]. Recent work has focused on exploring alternative virtual representations of the keyboard and hands [25,34] and using mixed-reality systems to overlay camera data of the user's hands with virtual content [31]. Yet these approaches require the user to be seated and do not work for room-scale VR or AR, the scenarios with the highest potential immersion and use of physical navigation to enhance presence.…”
Section: Introductionmentioning
confidence: 99%